A Highly Fluorescent Dinuclear Aluminium Complex with Near-Unity Quantum Yield** - Portwich, Flavio L.; Carstensen, Yves; Dasgupta, Anindita; Kupfer, Stephan; Wyrwa, Ralf; Goerls, Helmar; Eggeling, Christian; Dietzek, Benjamin; Gräfe, Stefanie; Waechtler, Maria; Kretschmer, Robert (Angewandte Chemie International Edition, 2022)
The high natural abundance of aluminium makes the respective fluorophores attractive for various optical applications, but photoluminescence quantum yields above 0.7 have yet not been reported for solutions of aluminium complexes. In this contribution, a dinuclear aluminium(III) complex featuring enhanced photoluminescence properties is described. Its facile one-pot synthesis originates from a readily available precursor and trimethyl aluminium. In solution, the complex exhibits an unprecedented photoluminescence quantum yield near unity (Φabsolute 1.0±0.1) and an excited-state lifetime of 2.3 ns. In the solid state, J-aggregation and aggregation-caused quenching are noted, but still quantum yields of 0.6 are observed. Embedding the complex in electrospun non-woven fabrics yields a highly fluorescent fleece possessing a quantum yield of 0.9±0.04.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Aluminium; Dinuclear Complexes; Fluorophores; Luminescence; Quantum Yield